Teaching Performance and its Contradictions in Ecuadorian High School Institutions (Docentes 2.0 Journal, 2023)
To improve student training processes, indispensable aspects of children's education and adolescents must be considered. Teaching performance is part of the educational quality standards; therefore, the present research aimed to verify certain contradictions in research related to teaching performance in secondary education institutions with the results obtained from evaluations applied to teachers and students. The methodology used was based on the inductive, positivist paradigm with phenomenological design, qualitative approach, and the exploratory and cross-sectional type where criteria were obtained based on teachers' experience (seven as a study group) on educational aspects. The technique used to collect information was an inquiry and structured interview with specific questions on research aspects applied to teachers from different educational institutions. The results show favorable and unfavorable aspects of teaching performance; among the main ones, teachers are disinterested in the student's learning. They look for individual interests unrelated to the educational field, teachers with academic excellence that look for new paradigms of teaching methodologies, teachers with the absence of vocation, education that has been evaluated in the last years, and teacher training that is dissociated from the area of knowledge. In conclusion, educational training at the country level has decreased. The authorities must modernize educational processes to increase educational standards gradually.
Keywords: Teaching performance; contradictions; inquiry; phenomenology; qualitative